Chip pattern, burr and surface roughness in laser assisted micro milling of Ti6Al4V using micro ball end mill - Z. Mohid; E.A. Rahim (Journal of Mechanical Engineering and Sciences, 2018)
The effectiveness of laser heating could easily fluctuates when the uncut chip thickness are extremely inconsistent. In the case of using micro ball end mill tool, rubbing mechanism is inevitable due to its radial shape geometry. Furthermore, the scenario could be worst when the workpiece is a ductile material which has low thermal conductivity such as Ti6Al4V. Thus, characterization study was carried out to evaluate the feasibility of micro ball end mill in laser assisted micro milling operation. The chip, burr and surface roughness from conventional and laser assisted micro milling were compared and discussed. It is understood that the chip pattern indirectly gives significant influence to the effectiveness of laser assisted micro milling technique. With tool edge radius of 2 × 10-3 mm, feed value of 3.0 × 10-3 mm produced more consistent surface roughness compared to feed value of 2.1 and 4.2 × 10-3 mm. The machining parameters which produced continuous and conical chips ended up with sever burr formation and surface roughness inconsistency.